VISUAL COMMUNICATION MEDIA DESIGN AS A PROMOTIONAL STRATEGY FOR THE 'SEPATU KEDAS' SHOE CLEANING SERVICE IN DENPASAR - I Ketut Sassu Budi Satwam; Chandra Ramandha Putra (Yayasan Sinergi Widya Nusantara, 2025)
Purpose: This design aims to design visual communication media in the form of posters, brochures, goodie bags, sign boxes, motion graphics, which function as promotional media for Kedas Shoes services. Research methods: The design of this visual communication media uses a qualitative approach with primary and secondary data collection. This qualitative approach includes data collection through interviews, observations, literature, and documentation Findings: The design stage resulted in four promotional media: posters, brochures, goodie bags, and Instagram posts, which have gone through an evaluation and revision process to strengthen the visual identity and communication of Sepatu Kedas services. The design process was carried out by applying the modern flat design visual concept, using a color palette of red, orange, white, black, bright gray, and sans-serif typography that is applied consistently across all media. Implications: After being refined, the final design received approval from the owner of the Kedas Shoes business and was declared suitable for use as a print and digital promotional medium.